Revestimento de piso com porcelanato: estudo sobre especificação e execução baseado nas percepções dos profissionais envolvidos - Muniz, Andreia Fernandes (2012)
The Brazilian ceramic tile stands out in national and international scene with a production of 753.5 million square meters and a domestic consumption of 699.60 million square meters in 2010. Growth in production and consumption, respectively, 32.57% and 58.14% compared to 2005 (ANFACER, 2011). In this context relates to the porcelain, whose production in 2010 was 8.0% (60 million square meters) of the total production of ceramic plates. In 1999 this index was approximately 0.8% (Menegazzo et al., 2000). This growth is associated with its production process and its technical and aesthetic characteristics, which made it a suitable option for specifying different types of works. However, the specification of the porcelain is not yet understood by those involved. Furthermore, the shape is the same laying of the tiles, which can lead to pathology. On porcelain, the objective is to demonstrate how the specification is made by manufacturers in catalogs, how to evaluate the specification and use of catalogs by design professionals, know how to market and see what the problems in implementing the flooring with porcelain. Expected to contribute to the adequacy of standards catalogs, making the query tools in the acquisition of the coating by the consumer and the stage of specification, made by design professionals. For the execution stage, attest to the need to develop a specific standard for implementation of the porcelain coating, suitable for the specific properties of porcelain. The methodology includes review of the state of the art and field research through questionnaires, personal interviews with the professionals involved. The survey results show that the catalogs are incomplete, design professionals use the experience of sellers to specify the execution of the work is flawed, the settlers are not qualified to perform standard and ceramic coating needs to have specific recommendations for implementation of porcelain.